Wind-driven Coastal Upwelling Along South of Sulawesi Island - Abdullah Habibi; Riza Yuliratno Setiawan; Akhmad Yusuf Zuhdy (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2010)
The sea in the vicinity of south of Sulawesi Island (SSI) is influenced by monsoon winds. The present observation shows that coastal upwelling in the region is a dominant process leading to high chlorophyll-a (Chl-a) concentration during southeast (SE) monsoon season. Southeasterly monsoon winds are responsible for the upwelling formation.The objective of the reseach was to describe the wind-driven upwelling occurrence.  The bloom increases gradually, starting in May and climbing up to peak value (1.1 mg/m3) in August, then weakens in September. By utilizing a combination of satellite data of sea surface wind vector, sea surface temperature (SST), and surface Chl-a, the physical mechanism of the coastal upwelling in the SSI is investigated. Keywords : coastal upwelling, satellite remote sensing, wind speed, SST, Chl-a, south of Sulawesi island. Perairan  di  sekitar  selatan  Pulau  Sulawesi  dipengaruhi  angin  monsoon.  Observasi  menunjukkan  bahwa upwelling pantai di perairan tersebut merupakan proses dominan yang menyebabkan meningkatnya konsentrasi klorofil-a selama musim monsoon tenggara. Tujuan penelitian ini adalah menggambarkan kejadian wind-driven upwelling. Angin monsoon dari tenggara adalah penyebab terbentuknya upwelling. Konsentrasi klorofil-a naik secara bertahap, dimulai di bulan Mei dan mencapai maksimum (1.1 mg/m3) di bulan Agustus, kemudian berkurang  di  bulan  September.  Menggunakan  kombinasi  data  satelit  dari  angin  permukaan  laut,  suhu permukaan laut, Chl-a permukaan, mekanisme fisik dari upwelling pantai di perairan di selatan Pulau Sulawesi Kata kunci :  upwelling pantai, satelit penginderaan jauh, kecepatan angin, suhu permukaan laut, klorofil-a, selatan Pulau Sulawesi.